Analysis of the Use of Industry 4.0 Technologies in the Enterprises of European Union Countries - Magdalena TUTAK (Communications of International Proceedings, 2021)
Current changes in the global economy cause manufacturing and service companies to increasingly use technologies closely identified with the concept of Industry 4.0. These technologies are widely recognized as pillars of Industry 4.0, and their use allows for gaining a competitive advantage. They are closely related to the development of information systems, the Internet and networks. The process of technological change has covered virtually all regions of the world, including the European Union. The great diversity of the EU countries makes that these technologies be implemented to a different extent in each country. Due to the common economic policy, it is important to determine the degree of use of these technologies in enterprises of individual EU countries. The aim of the study was to analyze and evaluate the degree of utilization of these technologies in manufacturing and service companies employing more than 10 employees in 27 EU countries. The study was also aimed at determining the correlation between individual technologies implemented in these companies. Descriptive statistics methods, the Gini concentration coefficient, the Lorenz curve and the Pearson's linear correlation coefficient were used for the study. The analyses were conducted for data from 2019. The results show that Industry 4.0 technologies are used to the greatest extent by companies located in Finland, Denmark, Italy, Sweden, Belgium, the Netherlands, and Malta, and to the least extent – in Romania, Bulgaria, Greece, and Hungary.
Keywords: Industry 4.0; technologies of Industry 4.0; European Union Countries